Boron(III), Aluminium(III) and Arsenic(III) Derivatives of 1-Hydroxy-2-Naphthoic and 3-Hydroxy-2-Napththoic Acids. - GUPTA, YASHMANI; GANGWAR, TRIPTI; CHANDRA , MADHUP (Asian Journal of Chemistry, 2010)
Several elemento(III) derivatives of 1-hydroxy-2-naphtoic and 3-hydroxy- 2-naphthoic acids have been prepared by the interaction of boron-, aluminium- or arsenic triisopropoxide with the latter in various stoichiometric ratios viz. 1 : 1, 1 : 2 and 1 : 3 involving alcoholysis reactions in benzene/toluene medium. The compounds thus prepared were obtained generally as coloured solids, with some of them being hygroscopic. All these compounds have been characterized by azeotrope and elemental analyses, as well as by IR and PMR spectral measurements.